Rattanakosin yuk prapprung prathet, Pho. So. 2394-2475 - Pharadi Mahakhan (Krung Thep Maha Nakhon : Thai Watthana Phanit, 1984)
History of Bangkok, 1851-1932.
In Thai.
Bibliography: p. [169]-177.
Keywords: Bangkok (Thailand) -- History